The potential of bacteriocin typing in the study of Clostridium perfringens food poisoning. Issue 12 (December 1982) - Watson, G N; Stringer, M F; Gilbert, R J; Mahony, D E
Abstract : A range of 49 bacteriocins was used to type 311 strains of Clostridium perfringens isolated from food poisoning outbreaks. Strains of same serotype within an outbreak showed similar patterns of susceptibility to bacteriocins, whereas strains of different serotype isolated from different sources produced many variations in bacteriocin susceptibility patterns. The 311 strains, along with isolates from a wide range of sources were screened for their ability to produce bacteriocins. A much greater proportion of the strains from food poisoning outbreaks was bacteriocinogenic than were isolates from human and animal infections, various foods and the environment.